Transcriptomic Signatures of Antibody-mediated Rejection in Early Biopsies With Negative Histology in HLA-incompatible Kidney Transplantation - Hruba, Petra; Klema, Jiri; Mrazova, Petra; Girmanova, Eva; Jaklova, Katerina; Voska, Ludek; Kment, Martin; Mackova, Martina; Osickova, Klara; Hanzal, Vladimir; Halloran, Philip F; Viklicky, Ondrej (Transplantation direct, 2025)
BACKGROUND: Presensitized patients with circulating donor-specific antibodies (DSAs) before transplantation are at risk for antibody-mediated rejection (AMR). Peritransplant desensitization mitigates but does not eliminate the alloimmune response. We examined the possibility that subthreshold AMR activity undetected by histology could be operating in some early biopsies. METHODS: Transcriptome of kidney allograft biopsies performed within the first month in presensitized patients (DSA+) who had received desensitization and did not develop active/probable AMR by histology (R-) was compared with biopsies showing active/probable AMR (R+/DSA+). As negative controls, biopsies without rejection by histology in patients without DSA at transplantation were used (R-/DSA-). RNA sequencing from biopsies selected from the biobank was used in cohort 1 (n = 32) and microarray, including the molecular microscope (Molecular Microscope Diagnostic System [MMDx]) algorithm, in recent cohort 2 (n = 30). RESULTS: The transcriptome of R-/DSA+ was similar to R+/DSA+ as these groups differed in 14 transcripts only. Contrarily, large differences were found between both DSA+ groups and negative controls. Fast gene set enrichment analyses showed upregulation of the immune system in both DSA+ groups (gene ontology terms: adaptive immune response, humoral immune response, antigen receptor-mediated signaling, and B-cell receptor signaling or complement activation) when compared with negative controls. MMDx assessment in cohort 2 classified 50% of R-/DSA+ samples as AMR and found no differences in AMR molecular scores between R+ and R- DSA+ groups. In imlifidase desensitization, MMDx series showed a gradual increase in AMR scores over time. CONCLUSIONS: Presensitized kidney transplant recipients exhibited frequent molecular calls of AMR in biopsy-based transcript diagnostics despite desensitization therapy and negative histology.